Crack Growth Simulation in Corrugated Plate Using XFEM - Laftah, Rafil Mahmood; Abdulwahab, Qusai Talib (Basrah Journal for Engineering Sciences, 2017)
Corrugated plates play an important role in many modern constructions applications. Being the main components like piles or stiffeners means they quite often subjected to high levels of stresses. The presence of flaw or crack in the structure of loaded corrugated plate may lead to the situation of crack growth and then catastrophic failure. Extended Finite Element Method is used to avoid remeshing during crack growth simulation. In order to characterize crack growth in corrugated plate two methods were used which are virtual crack closure method and cohesive segments method. Two case studies were investigated in this study. In the first case the material behavior is assumed to be linear elastic, while in the second one the material behavior is assume to be elastic-plastic. The results obtained using the two methods showed a very good agreement both in linear elastic and elastic plastic cases.